A representação midiática-institucional dos movimentos sociais na Folha de São Paulo - Rodrigues, Rafael Alencar (2017)
The main purpose of this paper is to analyze the media-institutional representation of social movements in Folha de São Paulo. The analysis period covers the month of March, 2015. The content analysis method was used for the interpretation of the sample. The idea is to perceive how the interface between social movements and the media has been given, and the media according to Bourdieu has become a gateway to public existence, and, for this reason, these social subjects have planned their actions in order to interest the Mass communication vehicles. The analysis concluded that only those movements that are in political-ideological harmony with the newspaper acquire a positive representation. However, what they speak about is determined by this representation. Therefore, institutionalized media is more than an arbitrator of public existence, because it also determines and influences the discourses publicized by social movements.